2017
DOI: 10.1007/s00702-017-1741-8
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral thalamic deep brain stimulation for essential tremor in elderly patients

Abstract: The purpose of this study was to assess the influence of age on thalamic deep brain stimulation (DBS) in essential tremor (ET). Tremor, cognition, mood and adverse events in patients with thalamic DBS for ET were evaluated in 26 consecutive patients with established standardized methods for tremor and cognition. Twelve patients <70 and 14 patients ≥70 years were included and followed for 2 years. Clinical outcomes did not differ significantly. DBS seems to be safe and effective for ET independent of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 13 publications
0
21
1
Order By: Relevance
“…In one study, there was an improvement of simple reaction time when the DBS was turned on (Heber et al, 2013). In another study, there were improvements in attention and general cognitive functions (Klein et al, 2017). Our study found while the age at surgery had no significant influence, the working memory improved after DBS in ET patients who developed tremors at a younger age.…”
Section: Discussioncontrasting
confidence: 39%
“…In one study, there was an improvement of simple reaction time when the DBS was turned on (Heber et al, 2013). In another study, there were improvements in attention and general cognitive functions (Klein et al, 2017). Our study found while the age at surgery had no significant influence, the working memory improved after DBS in ET patients who developed tremors at a younger age.…”
Section: Discussioncontrasting
confidence: 39%
“…After screening titles and abstracts, 479 potentially relevant articles were identified, and the full text was assessed against the inclusion criteria. Finally, 240 articles were chosen to be included in this meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…However, these declines were only found with stimulation turned off. 33 Some reported studies have found no cognitive change related to DBS in the thalamic area, 22,27 while others have shown that low-frequency stimulation of the ventrolateral nucleus (VL) has less impact on phonemic and semantic fluency than high-frequency stimulation. 35 In all of the studies we have reviewed, the authors concluded that thalamic stimulation for ET is safe and does not affect higher cognitive processes.…”
mentioning
confidence: 99%